Fisherman’s wage perspective with theory of ferdinand lassalle and ji’alah - Ayu Wulandari Daud; Aning Kesuma Putri Syukri (INOVASI, 2022)
The Ji’alah (profit-sharing system) between a shipowner and a deckhand does not guarantee that a deckhandwill receive a decent wage. Catches obtained must be paid back for the use of factors of production used for fishing businesses, even to pay for capital and debt obtained from shipowners.Because fisheries are still found violations of human rights and employment, the Republic of Indonesia Minister of Maritime Affairs and Fisheries Regulation number 35 of 2015, one of which regulates wage systems and standards, refers to applicable laws, such as the provision of minimum wages (Ferdinand Lassale Theory).So the purpose of this study is to look at the fishermen's perspective on the profit-sharing system applied in the Syariah Economy called Jia'alah and the minimum wage derived from Lassale's Ferdinan Theory.So the purpose of this study is to look at the perspectives of 50 fishermen's in Central Bangka Regency and 50 fishermen's in South Bangka Regency regarding the profit-sharing system applied in the Islamic economy called Jia'alah and the minimum wage derived from Lassale's Ferdinan Theory.The analysis of this research is qualitative by using a SWOT analysis. The interview results show that 95 percent of fishermen have the perspective that the profit-sharing system is still fair compared to using the minimum wage system.